frequency and significance of antibodies to asialoglycoprotein receptor in patients with autoimmune hepatitis - AL-Obeidy, Eman Sh.; Al-Derzi, Aida R.; Al-Ani, Waleed (Journal of the Faculty of Medicine Baghdad, 2008)
Background: The asialoglycoprotein receptor (ASGP-R)